Aplikasi Pengolahan Citra Digital untuk Mengontrol Saklar Berdasarkan Letak dan Warna Huruf - Totalis, Herry; Christyono, Yuli; Zahra, Ajub Ajulian (Departemen Teknik Elektro, Universitas Diponegoro, 2010)
The use of wireless communication system as a communication medium in control system has been getting popular. Sending information is getting easier with wireless network for example internet. SMS technology has also been used in the house as remote control switch, but there are still many weaknesses including user must know the format of SMS text and have trouble when more and more switches are used. Beside location and condition of the switch in the house is not known directly. Therefore we need a system that can control house’s switch by knowing location and condition directly through pictures.The purpose of this final project research is to design and create a tool that can control switch remotely using wireless communications with the image display’s position of switch so that we can immediately find out controlled switch . Switch condition is analogue with condition of the microcontroller pin ATmega8535. In this final project the system is divided into two, namely transmitter and receiver. Transmitter section prepares house plans image data that has been processed and then sent to receiver while receiver interprets image data to determine commands to the microcontroller ATmega8535. Condition of switch can be seen on LED that is connected to microcontroller pin. Based on the test results, it is found that installation image character, changing the color of image character and scanning house plans image in accordance with determined run. Command are sent through serial port properly executed by microcontroller. There’s no error that occur during entire course of the program. In using of ad hoc networks have influencing factors that is the distance, type of laptops and barrier. Keyword : transmitter, receiver, house plans image, image character, ad hoc network, serial port, microcontroller ATmega8535